[Western Australia 1:50 000 photomosaic series]. 1848 II,. Mooka - Western Australia. Department of Lands and Surveys (Perth, W.A. : Dept. of Lands and Surveys, 1980)
An uncontrolled mosaic compiled in the format of the National topographic map series.
Keywords: Mooka (W.A.) -- Maps; Remote-sensing maps